Dual-Track Diplomacy Government-NGO: Solusi Alternatif dalam Masalah Perlindungan TKI di Malaysia - Sustikarini, Amalia (UI Scholars Hub, 2004)
This article offers a new paradigm in analyzing migrant worker problems in Indonesia, particularly about its relationship with Malaysia, as one of the most significant destination country for Indonesian migrant workers. Migrant workers issues must be analyzed with social economy, politics and humanitarian perspectives, to obtain a comprehensive view towards this never-ending problem. Diplomacy becomes a very important aspect if we want to discuss about the protection of Indonesian Migrants Worker. Indonesian Government needs to invite a further involvement of NGO to implement dual track diplomacy, since this problem is too complicated to be solved only by the government. This article is also supported with the historical background of the occurrence processes of the migrant worker in the world, and between Indonesia-Malaysia in particular.